Antecedent thermal injury worsens split-thickness skin graft quality: A clinically relevant porcine model of full-thickness burn, excision and grafting. Issue 1 (February 2017) - Carlsson, Anders H.; Rose, Lloyd F.; Fletcher, John L.; Wu, Jesse C.; Leung, Kai P.; Chan, Rodney K.
Highlights: Burn and excisional wounds were grafted and the effect on skin quality compared. Antecedent burn increased skin graft contraction and decreased skin quality. Antecedent burn increased inflammation, neovascularization, and scarring. The model can serve to evaluate future skin replacement or modulation strategies. Abstract: Current standard of care for full-thickness burn is excision followed by autologous split-thickness skin graft placement. Skin grafts are also frequently used to cover surgical wounds not amenable to linear closure. While all grafts have potential to contract, clinical observation suggests that antecedent thermal injury worsens contraction and impairs functional and aesthetic outcomes. This study evaluates the impact of antecedent full-thickness burn on split-thickness skin graft scar outcomes and the potential mediating factors. Full-thickness contact burns (100 °C, 30 s) were created on the backs of anesthetized female Yorkshire Pigs. After seven days, burn eschar was tangentially excised and covered with 12/1000th inch (300 μm) split-thickness skin graft. For comparison, unburned wounds were created by sharp excision to fat before graft application. From 7 to 120 days post-grafting, planimetric measurements, digital imaging and biopsies for histology, immunohistochemistry and gene expression were obtained. At 120 days post-grafting, the Observer Scar Assessment Scale, colorimetry, contour analysis and optical graft height assessments were performed. Twenty-nine porcine wounds were analyzed. All measured metrics of clinical skin quality were significantly worse ( p < 0.05) in burn injured wounds. Histological analysis supported objective clinical findings with marked scar-like collagen proliferation within the dermis, increased vascular density, and prolonged and increased cellular infiltration. Observed differences in contracture also correlated with earlier and more prominent myofibroblast differentiation as demonstrated by α-SMA staining. Antecedent thermal injury worsens split-thickness skin graft quality, likely by multiple mechanisms including burn-related inflammation, microscopically inadequate excision, and dysregulation of tissue remodeling. A valid, reliable, clinically relevant model of full-thickness burn, excision and skin replacement therapy has been demonstrated. Future research to enhance quality of skin replacement therapies should be directed toward modulation of inflammation and assessments for complete excision.